Cyclin B3 Deficiency Impairs Germline Stem Cell Maintenance and Its Overexpression Delays Cystoblast Differentiation in Drosophila Ovary. - Chen, D.; Zhou, L.; Sun, F.; Sun, M.; Tao, X. (International journal of molecular sciences, 2018)
It is well known that cyclinB3 (cycB3) plays a key role in the control of cell cycle progression. However, whether cycB3 is involved in stem cell fate determination remains unknown. The Drosophila ovary provides an exclusive model for studying the intrinsic and extrinsic factors that modulate the fate of germline stem cells (GSCs). Here, using this model, we show that DrosophilacycB3 plays a new role in controlling the fate of germline stem cells (GSC). Results from cycB3 genetic analyses demonstrate that cycB3 is intrinsically required for GSC maintenance. Results from green fluorescent protein (GFP)-transgene reporter assays show that cycB3 is not involved in Dad-mediated regulation of Bmp signaling, or required for dpp-induced bam transcriptional silencing. Double mutants of bam and cycB3 phenocopied bam single mutants, suggesting that cycB3 functions in a bam-dependent manner in GSCs. Deficiency of cycB3 fails to cause apoptosis in GSCs or influence cystoblast (CB) differentiation into oocytes. Furthermore, overexpression of cycB3 dramatically increases the CB number in Drosophila ovaries, suggesting that an excess of cycB3 function delays CB differentiation. Given that the cycB3 gene is evolutionarily conserved, from insects to humans, cycB3 may also be involved in controlling the fate of GSCs in humans.